Study on Relationship between Recruitment and Selection and Employee Performance in Technical Training Institutes in Kenya (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of the study was to establish the relationship between Recruitment and Selection and the employee performance in Technical Institutes in Kenya. Human resource is an important corporate asset and the overall performance of company depends on the way it is put to use. In order to realize company objectives, it is essential to recruit people with requisite skills, qualification and experience and while doing so Human Resource Managers need to keep present and future requirements of organization in mind. The technical training institutes have in the recent past, faced transformation, expansion, conversions/upgrading and competition from other service delivery organizations. The objective was be to find out the relationship between recruitment and selection, and employee performance in technical training institutes in Kenya. The research adopted both descriptive and correlational research designs and a mixture of an approach consisting of both qualitative and quantitative research methods. A sample size of three Technical Institutes in Kenya and comprising of 137 respondents was used. A linear regression analysis was used to explain the relationship between independent variables and dependent variable. The data was analyzed and presented using the statistical methods amongst them tables, bar graphs and pie charts. The results were used test and determine the relationship of the variables. The findings revealed that employee welfare and reward management had the greatest effect on performance. The findings of the research was that there was a significant positive relationship between recruitment and selection and employee performance.